Bikiniarze w „Przekroju”. Podwójna narracja - Stefańska, Katarzyna (Zagadnienia Rodzajów Literackich, 2023)
This article attempts to describe the first Polish subculture that appeared in the Polish People’s Republic in 1948–1956. Bikiniarze were characterized on the basis of 300 issues of the “Przekrój” magazine, published during the apogee of this subculture. The choice of this journal is justified by the desire to look at bikiniarze through the prism of a magazine which in communist times served as a “safety valve” and was not the right hand of the Polish authorities, which demanded the creation of a negative image of bikiniarze as presented in party press publications such as: “Sztandar Młodych”, “Trybuna Ludu”, or “Po Prostu”. Th e characteristics of the subculture focus mainly on the image of a man — a bikiniarz, who is a symbol of this subculture and includes both a specific way of dressing and behaving, as well as lifestyle. The article also touches on the issue of a certain ambiguity of “Przekrój” itself, which is visible in the example of the magazine’s attitude towards this subculture. This magazine played a certain game with censorship and resorted to various measures to smuggle non-propaganda content, including those about bikiniarze, who were oppressed by the authorities on its pages. This was done, for instance, by using: satire, fairy tales or poems.